Service oriented management – solutions for seizing market opportunities: x - Kuhn, Elvira (Management and Administration Journal, 2021)
In this paper we discuss the activities needed continually to adapt the enterprise in an ever changing environment. Our Thesis is, that it is not enough to observe the markets and to consider the consumer‟s needs, but it is also necessary to build up customer loyalty and to establish a relationship of trust with the clients in a dynamic evaluating process. In this connection clients will be customers or partners.